Compatibility of Buton rock asphalt with petroleum asphalt and their multi-scale ultraviolet aging behavior - Rao, Chaoyue; Jin, Duo; Zhu, Chongzheng; Zhang, Min; Lu, Weiwei; Lv, Songtao; Duan, Haihui (Frontiers in Built Environment, 2026)
IntroductionUltraviolet (UV) radiation is one of the primary environmental factors causing performance degradation of asphalt pavements, while the compatibility between modifiers and petroleum asphalt significantly influences the aging resistance of modified asphalt. This study aims to elucidate the compatibility between Buton rock asphalt (BRA) and petroleum asphalts as well as the influence of compatibility on UV aging behavior.MethodsThe compatibility of BRA (at a dosage of 30 wt%) with four base asphalts (Maoming Petrochemical 70# (70-A), Donghai 70# (70-B), Shuanglong 70# (70-C), and Panjin 90# (90-D)) was evaluated through physical property tests and dynamic shear rheometer (DSR) measurements. The thin-film oven test (TFOT) was employed to simulate short-term thermo-oxidative aging during construction, followed by multi-cycle variable-intensity UV aging to simulate long-term photo-oxidative aging during service. Viscosity, DSR, scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), and gel permeation chromatography (GPC) tests were used to analyze multi-scale ultraviolet aging behavior.Results70-A exhibits the best compatibility with BRA, with its modified asphalt (70-A-MA) showing a softening point of 50.5 °C (an increase of 11.0%), moderate viscosity growth (37.1%), and good storage stability. The increments in viscosity aging index and rutting factor aging index of 70-A-MA are lower than those of 90-D-MA, and 70-A-MA maintains lower surface crack density. FTIR analysis shows that the total growth rates of carbonyl and sulfoxide indices for 70-A-MA (70.4% and 42.5%) are significantly lower than those for 90-D-MA (202.0% and 131.7%); GPC results indicate that the total large molecular size (LMS) content increase for 70-A-MA (30.0%) is also lower than that for 90-D-MA (68.2%).DiscussionThese results demonstrate that the type of base asphalt is a key factor influencing its compatibility with BRA. Modified asphalt with superior compatibility exhibits better chemical stability and less severe aging damage. This study provides scientific guidance for the selection of base asphalt in BRA modification applications.